The Influence of Thinking Styles and Learning Styles on Student Learning Achievement - Ismail Ismail; Hasanuddin Hasanuddin; Andi Chandra (STAI Hubbulwathan Duri, 2023)
Thinking styles and learning styles are a person's unique identity in the learning process in order to achieve learning outcomes, one of which is learning achievement. This study aims to see the effect of thinking and learning styles on learning achievement in Islamic education at a private Islamic university in North Sumatra. The method used is quantitative. There are 2739 students as a population and 438 students as a sample. The instrument uses a Likert scale. The thinking style scale was adapted from Sternberg; namely, thinking style and student learning style variables will be measured using the Grasha Learning Style Inventory. The results showed that there was an influence of thinking styles and learning styles on learning achievement in Islamic Education at a private Islamic university in North Sumatra. There is a contribution between the dominant thinking style on student achievement (F = 29,393, p = .000) with an effect of 32.4%. There is a significant contribution from the dominant learning style to student achievement in Islamic education (F = 36,500, p = .000), with a contribution of 20.2%.